THE TYPOLOGY OF MOSQUE ARCHITECTURE IN WEST ACEH - Nurul Fakriah (Journal of Islamic Architecture, 2022)
Aceh is well known as the center of spreading Islam in South East Asia. West Aceh has contributed to present their best people in the history of the battle against colonialism when the heroic war in the past. Thus, Acehnese are considered a religious society. However, the research on the typology of significant Islamic buildings, such as mosques, has been very limited in this area. This study aims to determine the typology of mosques in West Aceh. This study was conducted based on observation data in West Aceh and a literature study. The number of twenty-five mosques is included in this study. The locations of mosques were in Meulaboh, the capital city of West Aceh, and in the rural area of West Aceh. The result shows that the typology of mosques in West Aceh has similarities with Masjid Raya Baiturrahman which stands in the capital city of Aceh. The similarities are found in the typology of the roof, door, window, column, and façade ornamentation. Meanwhile, the minaret did not have a significant influence on the typology of the mosques in West Aceh. There is still research to be done and data to be collected about other mosques in other areas in Aceh. Then, the date period of construction data should be added to give a comprehensive perspective of the influence.